Cholesterol at ages 6, 12 and 24 months: Tracking and associations with diet and maternal cholesterol in the Infant Cholesterol Study. (June 2021) - Øyri, Linn K.L.; Bogsrud, Martin P.; Kristiansen, Anne Lene; Myhre, Jannicke B.; Astrup, Helene; Retterstøl, Kjetil; Brekke, Hilde K.; Roeters van Lennep, Jeanine E.; Andersen, Lene F.; Holven, Kirsten B.
Abstract: Background and aims: There are indications for tracking of circulating total cholesterol concentration (TC) from childhood to later in life. An increased lifelong TC exposure increases the risk of developing atherosclerosis, however little is known about the determinants of TC early in life. We aimed to describe TC in Norwegian offspring aged 6, 12 and 24 months, and to explore if maternal TC, breastfeeding and offspring diet are associated with offspring TC. Methods: In this cross-sectional study, mothers of offspring aged 6 (n = 629), 12 (n = 258) and 24 (n = 263) months completed a questionnaire of the offspring's diet and took home-based dried blood spot samples from themselves and their offspring. The mothers and offspring participating at age 12 months also participated at age 6 months of the offspring. Results: Offspring TC showed a wide range in all three age groups. Twenty one percent of the offspring had TC ≥ 5.1 mmol/l. There was significant tracking of offspring TC from 6 to 12 months of age (r = 0.42, p  < 0.001). Maternal and offspring TC was positively associated in all age groups (0.20 ≤ β ≤ 0.40, p  < 0.001 for all). Breastfeeding was positively associated with offspring TC at ages 6 and 12 months (0.05 ≤ β ≤ 0.26, 0.001 ≤  p  ≤ 0.03), but not at age 24 months. Conclusions: The wide range in TC and probable tracking of TC from infancy to later in life highlights the importance of early identification of children with elevated TC who can benefit from preventive measures. Highlights: Increased lifelong cholesterol (TC) exposure increases the risk of atherosclerosis. TC showed a wide range in offspring aged 6, 12 and 24 months. There was significant tracking of offspring TC from 6 to 12 months of age. Maternal and offspring TC were positively associated. Breastfeeding and TC were positively associated at age 6 and 12, but not 24 months.